A Redescription of the Bulla, Antennae, and Mouth Parts of Female Clavella sp. (Copepoda: Siphonostomatoida: Lernaeopodidae) Infesting Wild Gadus morhua Using Scanning Electron Microscopy (SEM). (22nd December 2020) - Murray, Harry M.; Hanlon, Jacqueline M.; Marshall, Kimberly; Morris, Corey
Abstract : Many members of the Copepod family Lernaeopodidae are well-known parasites of gadids. This study reports on the occurrence of a lernaeopodid infestation of wild-sourced Gadus morhua sampled from separate inshore (Gilbert Bay, NL) and offshore (Virgin Rocks, NL) populations from Newfoundland, Canada. The majority of the parasites were observed to be associated with the buccal cavity, gill filaments, gill arch, and occasionally near the outer edge of the operculum. Anatomical analysis and detailed redescriptions of the parasite's functional anatomy (mouth parts, antennae, and bulla complex) using high-resolution SEM indicated that the parasite was most likely of the genus Clavella . New morphological details of the second antennae ornamentation, first maxillae, bulla complex, and the oral cone are provided and discussed with regard to their potential in taxonomic applications.